Determinants of Environmental Degradation in India: Fresh Insights - Tahir, Muhammad; Albahouth, Abdulrahman (مجلة العلوم الإدارية و الإقتصادية, 2025)
This study aims to investigate the impact of electric power consumption, trade openness, urbanization, and income per capita on environmental degradation. The paper focuses on the Indian economy and employs “Autoregressive Distributed Lagged Modeling Approach (ARDL)” and utilizes data from 1991 to 2023. Findings confirm the EKC hypothesis between income and CO2 for the Indian economy where CO2 initially rise with the increase income level, but eventually higher economic growth enhanced environmental outcomes. Similarly, our results show that urbanization has improved the environment while higher electric power consumption has degraded the environment. However, evaluations on the impact of trade openness show that it has an insignificant impact on the environment. The results have implications India that could be utilized for effective policy making by the government authorities of India to address environmental challenges.